Constructions du genre dans le roman policier « anti-norme » de Fred Vargas - Hynynen, Andrea (Romanica Silesiana)
Constructing Gender in Fred Vargas’s Anti-Normative Crime Fiction Fred Vargas’s crime novels do not fit into any established type of the crime genre. Defying the existence of an ordinary person, the author creates singular characters with odd behaviours and extraordinary capacities, partly in order to challenge gender norms. These characters question existing notions of femininity and masculinity, while at the same time revealing what the author believes to be traditional images of male and female attributes and behaviours, and thereby they implicitly reproduce. Physical appearance, weight in particular, is a central aspect of all female characters intended to challenge gender norms, whereas the male characters display a more diverse approach. The characterisation of such female protagonists seems to be directed primarily against a social norm defining femininity as “tallness, slimness and beauty,” whereas the extraordinary features of the male characters relate more clearly to previous models of investigators found in the crime genre. Key words: Fred Vargas, crime fiction, gender, literary genre. Le roman policier est marqué